Strategi Pemasaran Syariah dalam Menghadapi Pesaing pada Toko Mandiri Bangunan di Kecamatan Mungka Kabupaten Lima Puluh Kota - Nur Hanifa; Khadijah Nurani (Lembaga Yasin AlSys, 2026)
Although Sharia marketing strategies in dealing with business competition have received attention in various studies, studies that specifically discuss the integration of the Sharia marketing mix (9P) with SWOT analysis in MSMEs in the building materials store sector remain limited. This study aims to analyze the Sharia marketing strategy implemented by Toko Mandiri Bangunan in dealing with business competition in Mungka Subdistrict, Lima Puluh Kota Regency. This study employed a qualitative approach with a case study design, involving participants consisting of the owner and employees selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed descriptively and qualitatively through the stages of data reduction, data display, and conclusion drawing, and were supported by SWOT analysis using the IFAS and EFAS matrices. The results showed that the implementation of the Sharia marketing strategy had not yet been fully optimal, particularly in the aspects of price, promotion, service, and patience, thereby affecting the decline in sales in recent years. The SWOT analysis showed that the business position was in Quadrant I (Strength–Opportunity), indicating the potential to develop an aggressive strategy by utilizing internal strengths to seize external opportunities. These findings contribute to the development of Sharia marketing theory through the integration of a SWOT-based strategic approach while broadening understanding of the implementation of Sharia marketing in MSMEs. This study concludes that the consistent optimization of all elements of the Sharia marketing mix is very important for improving business competitiveness. The implications of this study include theoretical contributions to the development of the Sharia marketing literature and practical contributions for MSME actors in improving business competitiveness, while also opening opportunities for further research on Sharia-based digital marketing.